Safety of milk and whey from Zlatibor region in relation to aflatoxin M1 contamination: a seasonal study. (September 2019) - Milicevic, D; Jankovic, S; Muric, K; Petrovic, Z; Petronijevic, R; Raseta, M; Djinovic-Stojanovic, J
Abstract: The objectives of this study were to assess aflatoxin M1 (AFM1 ) contamination in cow and goat milk and whey samples collected from small dairy producers in rural areas of Zlatibor. The study involved a total of 60 samples of cow milk (n=15), cow whey (n=15), goat milk (n=15) and goat whey (n=15). In order to elucidate the distribution and stability of AFM1 during milk processing, cheese manufacturing trials were performed using cow milk naturally contaminated with different concentrations of AFM1 (<0.05 to >0.25μg kg −1 ). AFM1 concentrations were measured using a validated immunoassay method (ELISA). None of the samples of milk or whey collected from areas of Zlatibor were contaminated with AFM1 . Contrary to that, in all of the analysed samples of whey obtained from contaminated cow milk, AFM1 was detected. We conclude that whey contains 40-60% of the amount of AFM1 present in milk. The results obtained indicate the intensification of dairy production and the supplementation with commercial feed such as maize could be risk factors that impact on the AFM1 incidence in contaminated milk. In addition, our study demonstrates there is a potential health risk due to the consumption of whey obtained from contaminated milk.